Marinomonas mediterranea MMB-1 Transposon Mutagenesis: Isolation of a Multipotent Polyphenol Oxidase Mutant - Solano, Francisco (American Society for Microbiology, 2000)
Marinomonas mediterranea is a melanogenic marine bacterium expressing a multifunctional polyphenol oxidase (PPO) able to oxidize substrates characteristic for laccases and tyrosinases, as well as produce a classical tyrosinase. A new and quick method has been developed for screening laccase activity in culture plates to detect mutants differentially affected in this PPO activity. Transposon mutagenesis has been applied for the first time to M. mediterranea by using different minitransposons loaded in R6K-based suicide delivery vectors mobilizable by conjugation. Higher frequencies of insertions were obtained by using mini-Tn10 derivatives encoding kanamycin or gentamycin resistance. After applying this protocol, a multifunctional PPO-negative mutant was obtained. By using the antibiotic resistance cassette as a marker, flanking regions were cloned. Then the wild-type gene was amplified by PCR and was cloned and sequenced. This is the first report on cloning and sequencing of a gene encoding a prokaryotic enzyme with laccase activity. The deduced amino acid sequence shows the characteristic copper-binding sites of other blue copper proteins, including fungal laccases. In addition, it shows some extra copper-binding sites that might be related to its multipotent enzymatic capability.